2019
DOI: 10.1039/c9cy01907c
|View full text |Cite
|
Sign up to set email alerts
|

Framework-confined Sn in Si-beta stabilizing ultra-small Pt nanoclusters as direct propane dehydrogenation catalysts with high selectivity and stability

Abstract: Highly stable Pt/Sn-Si-beta catalysts were prepared via an improved post-synthesis method, exhibiting high catalytic activity, good selectivity and excellent stability for propane dehydrogenation to propene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 63 publications
2
45
0
Order By: Relevance
“…The spatial confinement can be realized with the aid of porous materials (i.e., zeolites, [ 21,22 ] metal–organic frameworks (MOFs), [ 23 ] covalent‐organic frameworks (COFs), [ 24 ] and nanostructured carbon [ 25 ] ) or within specific crystal structures. [ 26,27 ] Such delicate nanoscale structures can effectively confine the clusters, ensuring the formation of monodispersed MACs with high uniformity.…”
Section: Synthesis Of Macsmentioning
confidence: 99%
“…The spatial confinement can be realized with the aid of porous materials (i.e., zeolites, [ 21,22 ] metal–organic frameworks (MOFs), [ 23 ] covalent‐organic frameworks (COFs), [ 24 ] and nanostructured carbon [ 25 ] ) or within specific crystal structures. [ 26,27 ] Such delicate nanoscale structures can effectively confine the clusters, ensuring the formation of monodispersed MACs with high uniformity.…”
Section: Synthesis Of Macsmentioning
confidence: 99%
“…The confinement has been shown to be crucial to enhance the propane conversion and the propene selectivity. Dealuminated Hβ (SiO 2 /Al 2 O 3 = 25) was used to encapsulate Sn species existing in tetrahedral coordination states into the framework of dealuminated beta (Si-beta) [70]. The strong Pt-Sn (IV) interactions inhibited the coke formation, while high dispersion of the ultrasmall nanoclusters inhibited the sintering of Pi clusters [71].…”
Section: Support Morphologymentioning
confidence: 99%
“…Both studies reported the framework Sn sites facilitate the high dispersion of the Pt species. Wang et al . reported their optimized catalyst (0.3 wt % Pt, 0.5 wt % Sn) lost only 13 % of its initial propene formation rate over 12 h at 600 °C and that it was stable over four reaction cycles at 550 °C with >99 % selectivity to propylene.…”
Section: High Temperature Alkane Conversionmentioning
confidence: 99%